Analisis Strategi Peningkatan Kinerja Pelayanan Kerja Sama dan Humas dengan Metode SWOT dan QSPM di Kawasan CSC-BG LIPI - Susanti, Ika (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2022)
The result of public satisfaction index of cooperation and public relations services in the CSC-BG LIPI area shows that the service quality is still in poor condition and there is a gap between performance and importance of science service. This study aimed to determine the correct strategy to improve service performance and researcher’s trust in CSC-BG LIPI’s area service. This study used descriptive qualitative approach, with triangulation data from participatory observation, in-depth interviews, and Focus Group Discussion methods. The data were analyzed with the SWOT instrument to determine alternative performance improvement strategies, and QSPM to determine the priority of performance improvement strategies. The results of the IE analysis was an internal value of 2.515 and an external value of 2.420. These result showed that the position was in the growth strategy that suitable to keep current good service performance and to vary on specific service product which had poor performance. The results of the SWOT and QSPM analysis showed that the influence of external strategic factors was greater than internal strategic factors. This influence affected service performance improvement strategies that focus on managing opportunities against threats. The priority of this strategy lied in service, infrastructure, competency, function and authority of CSC-BG LIPI area.